2012
DOI: 10.1186/1479-5876-10-s1-s2
|View full text |Cite
|
Sign up to set email alerts
|

An induction of microRNA, miR-7 through estrogen treatment in breast carcinoma

Abstract: BackgroundEstrogen plays an important role in the development of estrogen-dependent breast carcinoma. Recently, several studies demonstrated a possible involvement of several micro RNAs (miRNAs) in the development of resistance to endocrine therapy in breast cancer patients, but the correlation between estrogen actions and miRNA expression in breast carcinoma still remains largely unknown. Therefore, in this study, we examined the in vitro effects of estrogen upon miRNA expression profiles in breast carcinoma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 31 publications
(35 reference statements)
1
34
0
1
Order By: Relevance
“…Furthermore, the combined inhibition of ER and EGFR caused antiproliferative effects in cancer cells (Stabile et al ., 2005). However, in MCF‐7 breast cancer cells, E2 treatments were detrimental to EGFR expression in an ERα‐ and miR‐7‐dependent manner (Masuda et al ., 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the combined inhibition of ER and EGFR caused antiproliferative effects in cancer cells (Stabile et al ., 2005). However, in MCF‐7 breast cancer cells, E2 treatments were detrimental to EGFR expression in an ERα‐ and miR‐7‐dependent manner (Masuda et al ., 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Also, miR-7 is expressed abundantly in human pancreas and endocrine cells and has a specific role in endocrine cell differentiation and function [10] . It has been demonstrated that miR-7 is a tumor suppressor in breast, lung and ovarian cancers, and glioblastoma, mainly focusing on its relationship with EGFR [11][12][13][14][15] . Accumulating evidence shows that miR-7 can simultaneously target a variety of mRNAs involved in diverse signaling pathways in different tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, ethanol induced upregulation is also seen after estrogen treatment, such as in miR-27a and b (96). The fact that ethanol affected any particular miR in this study did not necessarily coincide with affects on other miRs that would be expected to change comcomitantly if ethanol action were limited to one specific pathway such as the estrogenic pathway: thus upregulated miRs such as miR-107, miR-424, miR-570, miR-618, and miR-760 (95), miR-21 (28), miR-34b (97), miR-98 (98), miR-19A and miR-24 (96), miR-26a and b (99), miR-17 (100,101), miR-7 (102), or miR-190a (103); or downregulated miRs such as miR-16, miR-143, or miR-203 (104). Interestingly, the latter is the opposite of what we observed with ethanol.…”
Section: Discussionmentioning
confidence: 99%